The mutualism–antagonism continuum in Neotropical palm–frugivore interactions: from interaction outcomes to ecosystem dynamics - Dracxler, Caroline; Kissling, W. Daniel (Biological reviews of the Cambridge Philosophical Society, 2022)
ABSTRACT Frugivory, that is feeding on fruits, pulp or seeds by animals, is usually considered a mutualism when interactions involve seed dispersal, and an antagonism when it results in the predation and destruction of seeds. Nevertheless, most frugivory interactions involve both benefits and disadvantages for plants, and the net interaction outcomes thus tend to vary along a continuum from mutualism to antagonism. Quantifying outcome variation is challenging and the ecological contribution of frugivorous animals to plant demography thus remains little explored. This is particularly true for interactions in which animals do not ingest entire fruits, that is in seed‐eating and pulp‐eating. Here, we provide a comprehensive review of Neotropical palm–frugivore interactions, with a focus on how frugivore consumption behaviour (i.e. digestive processing, fruit‐handling ability and caching behaviour) and feeding types (fruit‐eating, pulp‐eating and seed‐eating) influence interaction outcomes at different demographic stages of palms. We compiled a total of 1043 species‐level palm–frugivore interaction records that explicitly captured information on which parts of palm fruits are eaten by animals. These records showed consumption of fruits of 106 Neotropical palm species by 273 vertebrate species, especially birds (50%) and mammals (45%), but also fish (3%) and reptiles (2%). Fruit‐eating involved all four taxonomic vertebrate classes whereas seed‐eating and pulp‐eating were only recorded among birds and mammals. Most fruit‐eating interactions (77%) resulted in positive interaction outcomes for plants (e.g. gut‐passed seeds are viable or seeds are successfully dispersed), regardless of the digestive processing type of vertebrate consumers (seed defecation versus regurgitation). The majority of pulp‐eating interactions (91%) also resulted in positive interaction outcomes, for instance via pulp removal that promoted seed germination or via dispersal of intact palm seeds by external transport, especially if animals have a good fruit‐handling ability (e.g. primates, and some parrots). By contrast, seed‐eating interactions mostly resulted in dual outcomes (60%), where interactions had both negative effects on seed survival and positive outcomes through seed caching and external (non‐digestive) seed dispersal. A detailed synthesis of available field studies with qualitative and quantitative information provided evidence that 12 families and 27 species of mammals and birds are predominantly on the mutualistic side of the continuum whereas five mammalian families, six mammal and one reptile species are on the antagonistic side. The synthesis also revealed that most species can act as partial mutualists, even if they are typically considered antagonists. Our review demonstrates how different consumption behaviours and feeding types of vertebrate fruit consumers can influence seed dispersal and regeneration of palms, and thus ultimately affect the structure and functioning of tropical ecosystems. Variation in feeding types of animal consumers will influence ecosystem dynamics via effects on plant population dynamics and differences in long‐distance seed dispersal, and may subsequently affect ecosystem functions such as carbon storage. The quantification of intra‐ and inter‐specific variation in outcomes of plant–frugivore interactions – and their positive and negative effects on the seed‐to‐seedling transition of animal‐dispersed plants – should be a key research focus to understand better the mutualism–antagonism continuum and its importance for ecosystem dynamics.